Effects of culture conditions of immobilized recombinant Escherichia coli on cyclodextrin glucanotransferase (CGTase) excretionand cell stability - Che Man, Rohaida; Ismail, Ahmad Fauzi; Mohd Fuzi, Siti Fatimah Zaharah; Ghazali, Nazlee Faisal; Md Illias, Rosli (Elsevier, 2016)
The targeting of recombinant proteins for excretion into culture medium presents significant advan-tages over cytoplasmic expression. However, during the excretion of recombinant protein, caution mustbe taken in order to avoid cell lysis due to pressure build-up through overproduction of the expressedrecombinant protein in the periplasmic space. In the present study, recombinant Escherichia coli express-ing cyclodextrin glucanotransferase (CGTase) was immobilized by adsorption and entrapment in a poroushollow fiber membrane. The effects of culture conditions (post induction time, agitation rate and pH) onCGTase excretion, cell lysis and plasmid stability of immobilized cells were studied. The optimum postinduction time, agitation rate and pH were found to be 24 h, 200 rpm and pH 9, respectively. The immo-bilized cells exhibited a 2.8–4.6-fold increase in CGTase excretion, a 16–95% reduction of cell lysis anda 323–464% increase in plasmid stability compared with free cells. Hence, immobilizing E. coli using aporous hollow fiber membrane proved to be valuable for the excretion of a recombinant protein andincreased cell viability.